Spotlighting Eurovision as a political stage: Exploring how Turkey and Ukraine use the ESC to further their political agendas - Charlotte Gadea (Australian and New Zealand Journal of European Studies)
Beginning in 1956, The Eurovision Song Contest is the longest running television musical competition (Kivak, 2024). Not only does it showcase the talents of musical artists across Europe, but it is also a celebration of culture and a platform for countries to showcase their unique identities. By framing the contest in this context, it transcends simple entertainment, serving as a powerful tool for nations to further their political agendas. This essay will argue that the ESC can be strategically utilised by countries and individuals in order to promote their political interests and spotlight social issues through both performance and public discourse. By analysing Turkey’s 2003 win and both Ukraine’s 2005 and 2016 entries, an understanding of how music intersects with politics and how the contest acts as a communication device for these nations to share their cultural narratives can be arrived at. These performances provide a stage for countries to showcase their Europeanness, critique their own country's politics and highlight injustices committed by other nations.